Islamic Republic of Mauritania : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Statistical data and issues are discussed in this paper. Mauritania reached the completion point under the enhanced Initiative for Heavily Indebted Poor Countries. In July 2004, a new economic team took actions to tighten fiscal and monetary policies. The authorities intend to adopt sound principles for oil revenue management and tracking (various frameworks, such as the one proposed in the Extractive Industry Transparency Initiative, are under consideration). Executive Directors welcomed the authorities' willingness to prepare for the transition to a more flexible exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet